Analisis Hakikat, Prinsip, dan Landasan Pengembangan Kurikulum Pendidikan Agama Islam: Kajian Literatur: Analisis Hakikat, Prinsip, dan Landasan Pengembangan Kurikulum Pendidikan Agama Islam: Kajian Literatur - Luthfia Hanifatus Saiyidah; Agus Pahrudin; Agus Jatmiko; Koderi Koderi (Universitas Muhammadiyah Magelang, 2025)
This study was focused on analyzing the essence, principles, and foundations that serve as the basis for developing the Islamic Religious Education (PAI) curriculum through a review of recent literature. The method employed was library research, conducted by examining a range of scientific journals and books published within the last 5”“10 years. Based on the findings, it was identified that: (1) the essence of the PAI curriculum is grounded in theological foundations derived from the Qur’an and Sunnah, and is directed toward adapting to the demands of the 21st century; (2) the principles of curriculum development were found to emphasize contextual relevance, value integration, competency achievement, and flexibility in implementation; and (3) the foundations of curriculum development encompass philosophical, sociological, psychological, as well as technical and political dimensions of education. The reviewed literature also revealed that the implementation of the PAI curriculum still faces several challenges, such as the suboptimal readiness of teachers, the limited availability of adaptive teaching materials, and the need to integrate 21st-century skills into the learning process. Based on these findings, it is recommended that teacher capacity be strengthened through continuous training, the development of teaching materials based on local contexts and Islamic values from the Qur’an and Sunnah, and the enhancement of cross-stakeholder collaboration to ensure the relevance and effectiveness of the PAI curriculum implementation. Keywords: PAI Curriculum, curriculum essence, development principles, foundations, library research.